Assertion skills - tintypes (Santa Monica, Calif. : Salenger Educational Media, 1976)
Provides an introduction to assertion training, which is based on the premise that meekness and aggressiveness are undesirable behavior patterns. Designed to serve as a learning aid and to motivate viewers
Keywords: Assertiveness (Psychology)